A Critical Review on Black Phosphorus‐Based Photocatalytic CO2 Reduction Application. Issue 49 (26th July 2021) - Zhao, Guo‐Qing; Hu, Jun; Long, Xuan; Zou, Jiao; Yu, Jin‐Gang; Jiao, Fei‐Peng
Abstract: Energy shortages and greenhouse effects are two unavoidable problems that need to be solved. Photocatalytically converting CO2 into a series of valuable chemicals is considered to be an effective means of solving the above dilemmas. Among these photocatalysts, the utilization of black phosphorus for CO2 photocatalytic reduction deserves a lightspot not only for its excellent catalytic activity through different reaction routes, but also on account of the great preponderance of this relatively cheap catalyst. Herein, this review offers a summary of the recent advances in synthesis, structure, properties, and application for CO2 photocatalytic reduction. In detail, the review starts from the basic principle of CO2 photocatalytic reduction. In the following section, the synthesis, structure, and properties, as well as CO2 photocatalytic reduction process of black phosphorus‐based photocatalyst are discussed. In addition, some possible influencing factors and reaction mechanism are also summarized. Finally, a summary and the possible future perspectives of black phosphorus‐based photocatalyst for CO2 reduction are established. Abstract : Black phosphorus has been a hotspot in the field of photocatalytic CO2 reduction due to its distinctive potential advantages. This review summarizes recent synthesis methods and photocatalytic CO2 reduction applications of black phosphorus, the possible appearing challenges, and some future perspectives of these materials are also discussed. The aim is to provide certain reference to design black phosphorus‐based catalysts.